Associations between cyberbullying victimization and deviant health risk behaviors. Issue 2 (1st June 2019) - Graham, Roderick; Wood, Frank R.
Abstract: The primary aim of this study is to establish associations between cyberbullying victimization and health risk behaviors that have been traditionally linked to juvenile delinquency. These "deviant health risk behaviors" include drug use, alcohol use, and sex with multiple partners. A secondary aim is to compare the effects of cyberbullying on these deviant health risk behaviors to the effects of physical bullying. Models are estimated using the 2015 Youth Risk Behavior Survey conducted by the Center for Disease Control and Prevention (n = 15, 624). The findings showed that cyberbullying victimization is positively associated with each deviant health risk behavior predicted. The magnitude of this association increased when respondents reported being both cyberbullied and physically bullied. When comparing the effects of cyberbullying to physical bullying, the findings showed that respondents who were cyberbullied reported higher rates of each deviant health risk behavior. Establishing these associations is important for scholars and education professionals as they point to another pathway through which a young person can adopt delinquent or problematic behavior.